Learn more about

Refine search

Results (displaying matches 1-50 of 2284) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
336.a.172032.1 336.a \(y^2 + (x^3 + x)y = -x^6 + 15x^4 - 75x^2 - 56\) $G_{3,3}$ 0
644.a.2576.1 644.a \(y^2 + (x^2 + x)y = -5x^6 + 11x^5 - 20x^4 + 20x^3 - 20x^2 + 11x - 5\) $G_{3,3}$ 0
672.a.172032.1 672.a \(y^2 + (x^3 + x)y = -x^6 - 16x^4 - 75x^2 + 56\) $G_{3,3}$ 0
784.b.25088.1 784.b \(y^2 + (x^2 + 1)y = -x^6 - 3x^5 + 7x^4 + 2x^3 - 49x^2 + 41x - 9\) $G_{3,3}$ 0
816.b.52224.1 816.b \(y^2 + (x^3 + x)y = -x^6 - 12x^4 - 27x^2 - 17\) $G_{3,3}$ 0
847.d.847.1 847.d \(y^2 + (x^3 + x^2 + x + 1)y = -12x^6 - 15x^5 + 9x^4 + 31x^3 + 9x^2 - 15x - 12\) $G_{3,3}$ 0
847.d.456533.1 847.d \(y^2 + y = -x^6 - 9x^5 - 22x^4 + 3x^3 + 37x^2 - 24x + 4\) $G_{3,3}$ 0
936.a.1872.1 936.a \(y^2 + (x^3 + x)y = -x^6 - 9x^4 - 32x^2 - 39\) $G_{3,3}$ 0
961.a.961.1 961.a \(y^2 + (x^3 + x + 1)y = -x^6 - x^5 - 7x^4 + 74x^3 - 145x^2 + 99x - 33\) $G_{3,3}$ 0
961.a.961.2 961.a \(y^2 + (x^3 + x + 1)y = -x^6 + 2x^5 - 8x^4 + 12x^3 - 18x^2 + 12x - 7\) $G_{3,3}$ 0
1050.a.131250.1 1050.a \(y^2 + (x^2 + x)y = 3x^6 + 8x^5 + 15x^4 + 17x^3 + 15x^2 + 8x + 3\) $G_{3,3}$ 0
1083.b.87723.1 1083.b \(y^2 + y = -x^6 - 3x^5 - 8x^4 - 11x^3 - 14x^2 - 9x - 6\) $G_{3,3}$ 0
1083.b.390963.1 1083.b \(y^2 + y = -x^6 + 3x^5 - 50x^4 + 95x^3 - 14x^2 - 33x - 6\) $G_{3,3}$ 0
1104.b.141312.1 1104.b \(y^2 + (x^3 + x)y = -x^6 - 3x^4 + 29x^2 - 46\) $G_{3,3}$ 0
1253.a.1253.1 1253.a \(y^2 + (x^3 + x^2 + 1)y = -x^6 + 2x^5 - 33x^3 + 43x^2 + 15x - 330\) $\mathrm{USp}(4)$ 0
1269.b.102789.1 1269.b \(y^2 + (x^3 + x)y = -2x^6 - x^5 - 21x^4 - 8x^3 - 80x^2 - 16x - 103\) $\mathrm{USp}(4)$ 0
1344.a.4032.1 1344.a \(y^2 + xy = -x^6 - 12x^4 - 48x^2 - 63\) $N(G_{1,3})$ 0
1470.a.2940.1 1470.a \(y^2 + (x^2 + x)y = -x^6 + 2x^5 - 5x^4 + 4x^3 - 5x^2 + 2x - 1\) $G_{3,3}$ 0
1564.a.50048.1 1564.a \(y^2 + (x^3 + 1)y = -x^6 + 7x^5 + 8x^4 + 17x^3 + 8x^2 + 7x - 1\) $G_{3,3}$ 0
1680.a.16800.1 1680.a \(y^2 + (x^3 + x)y = -x^6 - 18x^4 - 136x^2 - 350\) $G_{3,3}$ 0
1795.a.224375.1 1795.a \(y^2 + (x^3 + x^2 + x)y = -x^6 - 8x^4 + 3x^3 - 23x^2 + 6x - 23\) $\mathrm{USp}(4)$ 0
1920.a.368640.1 1920.a \(y^2 + (x^3 + x^2 + x + 1)y = 5x^6 + 6x^5 + 17x^4 + 12x^3 + 17x^2 + 6x + 5\) $G_{3,3}$ 0
1923.a.1923.1 1923.a \(y^2 + (x^3 + x + 1)y = -x^6 + x^5 - 3x^4 + 2x^3 - 3x^2 + x - 1\) $\mathrm{USp}(4)$ 0
1988.a.3976.1 1988.a \(y^2 + (x^2 + x)y = 6x^6 + 16x^5 + 31x^4 + 35x^3 + 31x^2 + 16x + 6\) $G_{3,3}$ 0
2058.a.16464.1 2058.a \(y^2 + (x^3 + 1)y = -3x^6 + 5x^5 - 11x^4 + 10x^3 - 11x^2 + 5x - 3\) $N(G_{1,3})$ 0
2208.a.141312.1 2208.a \(y^2 + (x^3 + x)y = -x^6 + 2x^4 + 29x^2 + 46\) $G_{3,3}$ 0
2312.c.591872.1 2312.c \(y^2 + xy = -32x^6 - 31x^4 - 10x^2 - 1\) $G_{3,3}$ 0
2380.a.33320.1 2380.a \(y^2 + (x^2 + x)y = -14x^6 + 26x^5 - 56x^4 + 53x^3 - 56x^2 + 26x - 14\) $G_{3,3}$ 0
2484.a.9936.1 2484.a \(y^2 + (x^3 + x)y = -x^6 - 8x^4 - 24x^2 - 23\) $N(G_{1,3})$ 0
2640.a.2640.1 2640.a \(y^2 + (x^3 + x)y = -x^6 - 10x^4 - 40x^2 - 55\) $G_{3,3}$ 0
2688.a.172032.1 2688.a \(y^2 + y = -12x^6 - 36x^5 - 61x^4 - 62x^3 - 42x^2 - 17x - 4\) $G_{3,3}$ 0
2872.a.367616.1 2872.a \(y^2 + xy = -8x^6 - 28x^5 - 65x^4 - 88x^3 - 88x^2 - 51x - 20\) $\mathrm{USp}(4)$ 1
2890.b.49130.1 2890.b \(y^2 + (x^3 + 1)y = -x^6 + 5x^5 - 9x^4 + 4x^3 - 9x^2 + 5x - 1\) $G_{3,3}$ 0
2955.a.2955.1 2955.a \(y^2 + (x^3 + x)y = -x^6 - x^4 - x^3 - 3x^2 - 2x - 1\) $\mathrm{USp}(4)$ 0
3072.b.196608.2 3072.b \(y^2 = 2x^6 + 9x^4 + 13x^2 + 6\) $N(G_{1,3})$ 0
3120.b.199680.1 3120.b \(y^2 + xy = -80x^6 - 189x^4 - 149x^2 - 39\) $G_{3,3}$ 0
3168.a.684288.1 3168.a \(y^2 + (x^3 + x)y = -x^6 - 7x^4 - 17x^2 - 11\) $G_{3,3}$ 0
3200.e.819200.1 3200.e \(y^2 = -x^6 - 5x^4 - 7x^2 - 2\) $G_{3,3}$ 0
3280.a.3280.1 3280.a \(y^2 + (x + 1)y = -x^6 + 2x^5 - 4x^4 + 3x^3 - 3x^2 - 1\) $\mathrm{USp}(4)$ 0
3360.b.241920.1 3360.b \(y^2 + (x^2 + 1)y = -135x^6 - 96x^4 - 23x^2 - 2\) $G_{3,3}$ 0
3568.a.3568.1 3568.a \(y^2 + xy = -x^6 - 4x^5 - 9x^4 - 11x^3 - 9x^2 - 4x - 1\) $\mathrm{USp}(4)$ 0
3570.a.3570.1 3570.a \(y^2 + (x^3 + 1)y = -10x^6 + 23x^5 - 47x^4 + 50x^3 - 47x^2 + 23x - 10\) $G_{3,3}$ 1
3584.c.458752.1 3584.c \(y^2 + x^3y = x^6 - 4x^5 - 13x^4 - 22x^3 - 21x^2 - 12x - 4\) $N(G_{1,3})$ 0
3732.b.477696.1 3732.b \(y^2 + (x^3 + x + 1)y = -x^6 + 6x^4 + 10x^3 - 33x^2 - 14x + 3\) $\mathrm{USp}(4)$ 0
4046.a.4046.1 4046.a \(y^2 + (x^2 + x)y = -x^6 + 2x^5 - 3x^4 + 2x^3 - 3x^2 + 2x - 1\) $G_{3,3}$ 0
4158.a.16632.1 4158.a \(y^2 + (x^2 + x)y = -15x^6 + 32x^5 - 53x^4 + 64x^3 - 53x^2 + 32x - 15\) $G_{3,3}$ 0
4264.a.699296.1 4264.a \(y^2 + (x + 1)y = -3x^6 + 8x^5 - 16x^4 + 18x^3 - 17x^2 + 8x - 4\) $\mathrm{USp}(4)$ 0
4336.a.138752.1 4336.a \(y^2 + (x + 1)y = -11x^6 + 6x^5 + 22x^4 - 16x^3 - 6x^2 + 11x - 5\) $\mathrm{USp}(4)$ 0
4340.a.555520.1 4340.a \(y^2 + (x^3 + 1)y = -x^6 - 11x^5 - 24x^4 + 127x^3 - 24x^2 - 11x - 1\) $G_{3,3}$ 0
4482.a.4482.1 4482.a \(y^2 + xy = -3x^6 - 3x^5 - 9x^4 - 5x^3 - 8x^2 - 2x - 2\) $\mathrm{USp}(4)$ 0
Next

Download all search results for